2014
DOI: 10.2174/1573403x113099990001
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Collateral Artery Research

Abstract: In the event of obstructive coronary artery disease, collateral arteries have been deemed an alternative blood source to preserve myocardial tissue perfusion and function. Monocytes play an important role in modulating this process, by local secretion of growth factors and extracellular matrix degrading enzymes. Extensive efforts have focused on developing compounds for augmenting the growth of collateral vessels (arteriogenesis). Nonetheless, clinical trials investigating the therapeutic potential of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 114 publications
3
29
0
Order By: Relevance
“…This is not particularly useful, as arteriogenesis is more capable of restoring tissue blood supply than angiogenesis [15, 151], as collateral vessels have the capacity to carry a larger volume of blood than sprouting capillary networks [152]. At present, determining precise morphology is still dependent on post mortem angiography, as some collateral arteries (i.e.…”
Section: Radiotracer Imaging Of Arteriogenesismentioning
confidence: 99%
“…This is not particularly useful, as arteriogenesis is more capable of restoring tissue blood supply than angiogenesis [15, 151], as collateral vessels have the capacity to carry a larger volume of blood than sprouting capillary networks [152]. At present, determining precise morphology is still dependent on post mortem angiography, as some collateral arteries (i.e.…”
Section: Radiotracer Imaging Of Arteriogenesismentioning
confidence: 99%
“…In inflamed tissue, monocytes transform into macrophages where they clear pathogens, modulate tissue repair and healing [1], as well as support neovascularization progression [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…ϩϩ ) display anti-inflammatory characteristics (10,12,32). The role of intermediate monocytes (CD14 ϩϩ CD16 ϩ ) is less apparent.…”
Section: Cd16mentioning
confidence: 99%
“…In addition, we are limited to qualitative analysis of neovascularization due to the use of the angiogenesis molecular probe in one animal. However, numerous studies have previously shown that monocytes play an important role in modulating neovascularization (8,12,24).…”
Section: Cd62lmentioning
confidence: 99%